Turn off or tune in? What advice can SLTs, educational psychologists and teachers provide about uses of new media and children with language impairments?. (June 2014) - Durkin, Kevin; Conti-Ramsden, Gina
New media are commonplace in children's lives. Speech and language therapists (SLTs), educational psychologists and teachers are sometimes called upon by caregivers to provide advice on whether or how children and young people with language impairments should be encouraged to use these media. This article aims to illuminate some of the key issues and to review the implications of different types of advice that practitioners might provide. Four broad strategies are considered: Prohibition, Laissez-faire, Restriction, and Constructive use. Possible consequences of each strategy are outlined and it is proposed that Constructive use should be the strategy of choice. Reasons in favour of a constructive orientation include the benefits of joint engagement, enjoyment, cognitive and perceptual challenges and social motivation; effective uses can support educational attainment in young people with language impairments. Some areas where children and young people with language impairments need support with new media are noted. Decisions that we make about whether to constrain or support uses of new media have direct implications for the quality of young people's lives and futures. SLTs, educational psychologists and teachers have important roles to play in the development of better-informed policies and strategies concerning language impaired youngsters and digital media.